Factorial validity of a substance-use stigma scale in methamphetamine-using adults in China. (1st January 2020) - Chen, Shubao; Ma, Yuejiao; Cai, Weifu; Moretta, Tania; Wang, Xuyi; Liu, Tieqiao; Potenza, Marc N.
Highlights: Personal and perceived stigma may influence people with stimulant-use disorders. The Chinese substance-use stigma scale had acceptable fit indices and internal consistency. The scale had dimensions of personal and perceived stigma. A social distance scale had a good fit index and internal consistency as a separate domain. Multi-group analysis suggested scale invariance across drug-rehabilitation centers. Abstract: Background: Despite the large number of individuals who use substances of abuse and the stigma of such behaviors in China, scales have not been developed and validated for assessing substance-use stigma. Given its importance for targeting interventions, the aim of the present study was to validate a Chinese substance-use stigma measure including three dimensions of substance-use-disorder-related stigma (personal stigma, perceived stigma and social distance) by modifying a pre-existing scale measuring mental illness-related stigma and social distance. Methods: A convenience sample of eight-hundred-and-twelve individuals with substance abuse (aged 18–68 years) from different drug rehabilitation centers completed a self-reported survey including their demographics and drug use, and the stigma and social distance scales. The adapted, translated from English to Chinese, and back-translated scales were an 18-items stigma scale including personal stigma and perceived stigma subscales and a 5-items one domain social distance scale. Confirmatory factor analysis and multigroup confirmatory factor analysis tested factorial validity and measurement invariance of the scales, respectively. Results: For the stigma scale, by deleting one low correlation dimension (named "weak-not-sick"), personal stigma and perceived stigma showed acceptable fit indices and internal consistency with two dimensions (named "dangerous/unpredictable" and "social discrimination"), separately. The social distance scale showed good fit indices and internal consistency as a separate facet of stigma-related substance-use problems. Invariance of the model across drug-rehabilitation centers was found. Conclusions: The Chinese substance-use stigma scale may serve as a valuable tool for better understanding substance-use stigma among adults in China who abuse substances.